TOWARDS EUROPE 2007IDENTITY, INSTITUTION-BUILDING AND THE CONSTITUTION OF EUROPE - Ludger Kuhnhard (Ankara Avrupa Çalışmaları Dergisi)
The European Councıl ın Cologne (June 3-4, 1999) had defıned the mandate for the Intergovemmental Conference 2000. Four ıssues were to be resolved: - size and composıtıon of the European Commıssıon, - vveıghtıng of votes ın the Councıl; - extensıon of qualıfıed majonty votıng m the Councıl - further changes in the EU Treaties as far as they are related to the EU institutions in the context of the three issues mentîoned.The European Council in Nice (December 7-11, 2000), the longest and may be most problematic one in the history of the European Union, took - inter alia - the following decisions:1. As of January 2005, the Commission will be limited to 27 Commissİoners, thus leaving one Commissioner for each Union State.2. As of January 2005 a re-weighting of votes of current and future Union members will take place. Germany, France, Great Britain and Italy will have 29 votes each, thus leaving a formal equality between France and Germarty. Qualifîed majority will be reached if 255 of 342 weighted votes have been casted. The population will also be weighted. It will be necessary to find support of 73,5 percent of the population for a qualified majority (at current 71%). The new blocking majority will consist of 89 votes and 38 percent of EU’s population. This complex voting compromise might make it more difficult than ever to achieve results while in fact ne w veto mechanisms have been added.